Winning by His Grace: The Biography of Felix Ohiwerei - Emenyonu, Emmanuel (The Washington Nigerian Times, 2012)
Keywords: Biography; Christian biography; Biography; Nigerians; Nigeria; Ohiwerei; Felix; Businessmen; dept.acc; faculty_collection

The evolution of the relationship between the us financial accounting standards board and the international accounting standard setters: 1973-2008 - Kirsch, R.J. (Accounting Historians Journal, 2012)
Utilizing archival materials as well as personal interviews and correspondence with personnel of the Financial Accounting Standards Board (FASB) and International Accounting Standards Committee /Board (IASC/B), including former Board chairmen and staff members, this paper examines the development of the working relationships between the FASB and the IASC/B from their earliest interactions in 1973 through the transformation of the IASC into the IASB and the Convergence Program rooted in the 2002 Norwalk Agreement up to 2008. © 2012, Academy of Accounting Historians. All rights reserved.
14 citations (Crossref) [2023-10-31]
Keywords: dept.acc